Your injury, my accident: Talking at cross-purposes in rehabilitation after traumatic brain injury. (November 2013) - Body, Richard; Muskett, Tom; Perkins, Mick; Parker, Mark
Abstract Primary objective: To explore how traumatic brain injury (TBI) rehabilitation staff and adults who have sustained TBI refer during clinical interaction to the precipitating event. Design: Interviews conducted during the initial assessment phase of TBI rehabilitation were examined using Conversation Analysis. Participants: Participants were nine men and one woman, all of whom had sustained TBI of sufficient severity to warrant referral for community rehabilitation. Age range was 24–50 years (mean 35 years). The period between injury and interview was between 9 months and 20 years. Main outcomes and results: Analysis of interactions between rehabilitation staff and people with TBI indicated discrepancies in the way they refer to the original event. Staff tended to use 'head/brain injury' in contrast to the use by people with TBI of 'accident/crash'. There were also differences of expression in terms of 'ownership' (e.g. your injury vs. the injury) and 'agency' (the degree to which the person with TBI was portrayed as having been part of the process of sustaining the TBI). Conclusion: The implications of these discrepancies are discussed in relation to self-identity and insight after TBI. The possible impact of this terminological tension on the rehabilitation process is also discussed.